SATISFACTION WITH THE WORK PERFORMANCE OF PHRAPARIYATTHAM SCHOOL TEACHERS, GENERAL EDUCATION DEPARTMENTMUEANG DISTRICT UDON THANI PROVINCE - Vajasat, Sirina; Titavero, Phramaha Kraingkai (Journal of Social Science and Cultural, 2024)
The purpose of this research article was to study the level of the work performance satisfaction of Phrapariyattitham School teachers, General Education Department, Mueang District, Udon Thani Province. This research is survey research. The population and sample of the research was 33 teachers of Phrapariyattitham School, General Education Department, Mueang District. Obtained from selecting a purposive sample. Research tool is a 5-level rating scale questionnaire. The questionnaire's discrimination power ranged from 0.28-0.79 and the reliability was 0.91. Statistics used in data analysis were frequency, percentage, mean, standard deviation. Data were collected by asking for cooperation in answering questionnaires to sample groups. The results of the research found that the level of the work performance satisfaction of Phrapariyattitham School teachers, General Education Department, Mueang District, Udon Thani Province, 6 aspects. Overall and each aspect is at a high level. Considering each aspect by sorting the average values ​​from highest to lowest, it was found that teachers were most satisfied with their work in terms of occupation status, next is relationship with colleagues, the nature of work performed, working conditions, success of the work, and accepted and respected. Suggestions 1) Activities should be organized to promote students 2) There should be an opportunity for teachers to present their work 3) Special evaluations for teachers should be added 4) Teachers should be encouraged and given opportunities to do academic work 5) Activities should be organized to build relationships, create unity and 6) The environment should be improved to promote a working atmosphere